2013
DOI: 10.1021/ci3004545
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Acetohydroxyacid Synthase Inhibitors as Active Agents againstMycobacterium tuberculosisby Virtual Screening and Bioassay

Abstract: Acetohydroxyacid synthase (AHAS) has been regarded as a promising drug target against Mycobacterium tuberculosis (MTB) as it catalyzes the biosynthesis of branched-chain amino acids. In this study, 23 novel AHAS inhibitors were identified through molecular docking followed by similarity search. The determined IC(50) values range from 0.385 ± 0.026 μM to >200 μM against bacterium AHAS. Five of the identified compounds show significant in vitro activity against H37Rv strains (MICs in the range of 2.5-80 mg/L) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Numerous studies have shown that M. tuberculosis strains deficient in enzymes involved in various amino acid biosynthetic pathways are compromised in their ability to infect mice in comparison with the ability of parental strain (40 -42). In addition, several of these enzymes involved in amino acid biosynthesis are being currently explored for development of more potent antitubercular scaffolds (43)(44)(45)(46)(47)(48). L-Serine biosynthesis is an attractive and unexplored anti-microbial drug target because L-serine is not only involved in protein synthesis but also acts as precursor for various cellular metabolites (15, 49 -54).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that M. tuberculosis strains deficient in enzymes involved in various amino acid biosynthetic pathways are compromised in their ability to infect mice in comparison with the ability of parental strain (40 -42). In addition, several of these enzymes involved in amino acid biosynthesis are being currently explored for development of more potent antitubercular scaffolds (43)(44)(45)(46)(47)(48). L-Serine biosynthesis is an attractive and unexplored anti-microbial drug target because L-serine is not only involved in protein synthesis but also acts as precursor for various cellular metabolites (15, 49 -54).…”
Section: Discussionmentioning
confidence: 99%
“…The methyl thiazolyl tetrazolium (MTT) assay, which tests for cell proliferation and survival, was used in the present study, as previously described (14). Cells were incubated into 96-well culture plate, 5x10 3 cells in each well, to incubate for 72 h. In total, 50 µl MTT solution was added to each well and incubated at 37˚C for 4 h. Following incubation, MTT was aspirated and 150 µl dimethyl sulfoxide was added to each well to dissolve the formazan precipitate.…”
Section: Methodsmentioning
confidence: 99%
“…Tuberculosis caused by M. tuberculosis is the second leading cause of death, AHAS is recognized as a safe target for developing antimicrobial compounds. Oxygen atoms of benzoyl esters inhibitor form bonds with amino acids K203 and R326 of M. tuberculosis AHAS (Wang et al., ). These two residues leading to a strong binding affinity between inhibitor and AHAS are both conserved (Figure b).…”
Section: Resultsmentioning
confidence: 99%